Using Artificial Intelligence can increase academic fraud in Generation Z - Laturette, Kazia; Syahrani, Adelia; Octavica, Louisa (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2025)
Academic fraud, including cheating and the use of jockey services, has become a major issue in Indonesian higher education. This study aims to examine the influence of the five elements of the Fraud Pentagon Theory: pressure, opportunity, rationalization, competence, and arrogance, alongside religiosity on students' inclination to engage in academic fraud. This study examines the moderating influence of Artificial Intelligence (AI) on the relationship between these variables and academic misconduct. A quantitative research methodology was employed, administering questionnaires to 300 students from several colleges in East Java to gather survey data. The statistics demonstrate that four elements of the Fraud Pentagon: pressure, opportunity, rationalization, and competence, significantly influence academic misconduct, whereas arrogance and religiosity do not. AI, as a moderating variable, enhances the effect of skills on academic fraud while reducing the effect of opportunity. This study enriches academic literature by introducing AI as a moderating variable in the digital age and incorporating religion, a rarely explored factor.